ELECTRONIC PROCEEDINGS BY WRIT OF PAYMENT AS A MEANS TO IMPLEMENT THE PRINCIPLE OF SPEED OF PROCEEDINGS - Kotas, Sławomira (Człowiek w cyberprzestrzeni, 2020)
The aim of the study is to present the essence of electronic writ proceedings and to show if it can be an institution conducive to the speed of proceedings. The analysis will be conducted in relation to the guarantee of the right to a court and a fair trial.